I like myself! - Beaumont, Karen; Catrow, David (Orlando : Harcourt, 2004)
In rhyming text, a little girl expresses confidence and joy in her uniqueness, no matter her outward appearance.
Keywords: Self-esteem -- Fiction; Identity (Philosophical concept) -- Fiction; Stories in rhyme